Flow-Diversion Treatment of Unruptured Saccular Anterior Communicating Artery Aneurysms: A Systematic Review and Meta-Analysis - Cagnazzo, F.; Limbucci, N.; Nappini, S.; Renieri, L.; Rosi, A.; Laiso, A.; Tiziano di Carlo, D.; Perrini, P.; Mangiafico, S. (American Journal of Neuroradiology, 2019)
BACKGROUND: Flow diversion for anterior communicating artery aneurysms required further investigation.PURPOSE: Our aim was to analyze outcomes after treatment of anterior communicating artery aneurysms with flow-diverter stents.DATA SOURCES: A systematic search of 3 data bases was performed for studies published from 2008 to 2018.STUDY SELECTION: According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we included studies reporting anterior communicating artery aneurysms treated with flow diversion.DATA ANALYSIS: Random-effects meta-analysis was used to pool the following: aneurysm occlusion rate, complications, and factors influencing the studied outcomes.DATA SYNTHESIS: We included 14 studies and 148 unruptured saccular anterior communicating artery aneurysms treated with flow diversion. The long-term complete/near-complete (O'Kelly-Marotta C–D) occlusion rate was 87.4% (91/105; 95% CI, 81.3%–93.6%; I2 = 0%) (mean radiologic follow-up of 11 months). The treatment-related complication rate was 8.6% (14/126; 95% CI, 4%–13.1%; I2 = 0%), with morbidity and mortality rates of 3.5% (5/126; 95% CI, 2%–7%; I2 = 0%) and 2.5% (2/148; 95% CI, 0.3%–5%; I2 = 0%), respectively. Most complications were periprocedural (12/126 = 7%; 95% CI, 3%–11%; I2 = 0%). Thromboembolic events were slightly higher compared with hemorrhagic complications (10/126 = 6%; 95% CI, 2%–10%; I2 = 0% and 4/126 = 3%; 95% CI, 1%–6%; I2 = 0%). Branching arteries (A2 or the recurrent artery of Heubner) covered by the stent were occluded in 16% (7/34; 95% CI, 3.5%–28%; I2 = 25%) of cases. Pre- and posttreatment low-dose and high-dose of antiplatelet therapy was not associated with significantly different complication and occlusion rates.LIMITATIONS: We reviewed small and retrospective series.CONCLUSIONS: Flow diversion for unruptured saccular anterior communicating artery aneurysms appears to be an effective alternative treatment for lesions difficult to treat with coiling or microsurgical clipping. The treatment-related complication rate was relatively low. However, larger studies are needed to confirm these results.AcomAanterior communicating arteryASAacetylsalicylic acidATantiplatelet therapyCPclopidogrelIQRinterquartile rangeOKMO'Kelly-MarottaPRISMAPreferred Reporting Items for Systematic Reviews and Meta-Analyses